PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY TERHADAP PERSISTENSI LABA PADA SEKTOR PERTAMBANGAN - Stefany Sicilia Ahliawan; Juniarti Juniarti (Business Accounting Review, 2016)
Corporate Social Responsibility (CSR) provides many benefits to various parties.Research in CSR to earnings quality needs to be followed up because theoretically companies whouse CSR, the earnings quality from the company will increase. However, researches linking CSRto earning quality were still very rare. Therefore, this study was conducted to know the influenceof Corporate Social Responsibility (CSR) to the earning persistence on mining companies listed inthe Stock Exchange Indonesia of 2010 until 2014 with 56 samples by using SPSS version 22 as ameasuring tool.This research used CSR as independent variable and earning persistence as thedependent variable, and firm size and leverage as control variables. The results of this researchhad not proved yet the affect of CSR on earning persistence of companies on basic and chemicalindustry in Indonesia. The control variables used in this research also had not proved yet theiraffect on earning persistence in mining companies in Indonesia